2011
DOI: 10.1080/17461391.2010.545837
|View full text |Cite
|
Sign up to set email alerts
|

Effects of official youth taekwondo competitions on jump and strength performance

Abstract: The aim of this study was to investigate differences in athletes' (7 females, 10 males) motor performances (countermovement jump and handgrip) before and after official youth (13Á14 years) taekwondo matches. Exercise load was evaluated by means of the heart rate responses during the match. Independent of round and gender, during the competitions mean heart rate was 187 beats × min (1 (s 011). During the match, the frequency of heart rate responses above 85% of an individual's maximum heart rate was 77% (s 027)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…In a recent study, Menescardi et al (2019) reported that before scoring females performed posterior counterattacks while after that they performed spinning techniques. In this sense, it seems that Jones adapted her tactics to the characteristics of the bout situation and her opponents in an attempt to control them to score (Chiodo et al, 2012;Falco et al, 2014;Menescardi et al, 2015). Here, we can see an evolution of the tactics highlighted by Falco et al (2014), wherein the best way to react to a posterior counterattack is an indirect attack, while to a spinning kick a linear technique is better.…”
Section: Effective Three-point Actionsmentioning
confidence: 97%
“…In a recent study, Menescardi et al (2019) reported that before scoring females performed posterior counterattacks while after that they performed spinning techniques. In this sense, it seems that Jones adapted her tactics to the characteristics of the bout situation and her opponents in an attempt to control them to score (Chiodo et al, 2012;Falco et al, 2014;Menescardi et al, 2015). Here, we can see an evolution of the tactics highlighted by Falco et al (2014), wherein the best way to react to a posterior counterattack is an indirect attack, while to a spinning kick a linear technique is better.…”
Section: Effective Three-point Actionsmentioning
confidence: 97%
“…More specifically, padel game dynamics and match outcome could be exclusively analyzed for the final period of close (i.e., balance score) matches (Gomez, Gasperi, & Lupo, 2016). In addition, further studies on the analysis of physical performances (i.e., countermovement jump and handgrip) before and after official matches (Chiodo, Tessitore, Cortis, Lupo Ammendolia, & Capranica, 2012), time motion analysis (Conte, Favero, Lupo, Francioni, Capranica, & Tessitore, 2015) and game-based conditioning tests (Conte, Tessitore, Smiley, Thomas, & Favero (2016), physiological and psychological aspects (Casolino, Cortis, Lupo, Chiodo, Minganti, & Capranica, 2012), or integrated analyses which simultaneously consider heart rate, motion, and technical and tactical aspects (Lupo, Capranica, Cugliari, Gómez, & Tessitore, 2016), could substantially improve the knowledge of this emerging sport.…”
mentioning
confidence: 99%
“…The exercises included in the session were as follows [28]: -Suspended plank: feet (toes down) in foot cradles under the anchor point and forearms on the floor, keeping the body aligned for the planned time, without letting the hips or the back sag; -Sprinter's start knee-up: behind the ST device, grasping the handles with the straps underarms, bringing the rear knee up and forward, alternating the legs; -Chest press: behind the ST device, grasping the handles with extended arms, lowering the chest in push-up motion and returning to the start position; -Pike: starting from the suspended plank position, flexing at the hips slowly and under control until shoulders, hips, and legs are on a 90 • angle and returning to the start position; -Single leg squat: standing facing the ST device, grasping the handles with elbows bent at sides and extending the right leg forward, lowering the pelvis toward the floor and returning to the start position, alternating the legs; -T deltoid fly: standing facing to ST device, grasping the handles with extended arms, extending both arms to make a T shape pulling the body upright and keeping tension in the ST straps, then return to the starting position; -Oblique crunch: starting from the suspended plank position, lifting the pelvis and bringing the knees to the right elbow, returning to the starting position and bringing the knees to the left elbow; -Squat jump: standing facing the ST device, grasping the handles with the elbows bent at each side, lowering the pelvis toward the floor and return to the starting position, performing a jump at top of the movement; -Back row: stand facing the ST device, grasping the handles with extended arms, pulling the chest forward with a 45 • angle of the body with respect to the ground and then returning to the start position. In line with a similar research studying the acute effects on performance parameters [29][30][31][32][33], before (PRE) and after (POST) the ST session, power performances were evaluated by the means of squat (SJ) and countermovement (CMJ) jumps, whereas strength performances were evaluated by the means of maximum voluntary contraction (MVC) and maximum isometric grip force (handgrip). Previous findings suggested that distinct neural control mechanisms are employed for dominant and non-dominant arm movements [34] and that differences exist between dominant and non-dominant legs [35].…”
Section: Experimental Designmentioning
confidence: 97%